PEMETAAN KOMPETENSI PENGASUH TAMAN PENITIPAN ANAK DI TPA KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Nengsi Fitri; Wilson Wilson; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract. Research date collegcion was conducted in the second semester of teaching 2013/2014, through date collection instruments in the from of observasion sheets and interview caragivers. The results showed that of the 12 aspects and 24 caregivers overall competence in category of enough by an average 58.63%. whereas the competency of caregiver in child care center sub-district kuantan mudik kuantan regency in both categories and quite good. As for the indicators that are in both categories is the first indicator of the average of 67.86%, the secound indicator with anaverage of 66.67%, the third indicatorwith an avarage of 67.86%, indicator fourth with an avarage of 63.1%, the fifth indicator with an average of 66.67%, the sixth indicator with an average of 72.62%, the twelve indicators with an avarage 64.29%, thirteen indicator with an average 64,29%, the sixteenth indicator with and average 63.1%, the nineteenth indicator with an average of 61.9%, the twenty-two indicator with an average to 60.71%, and the twenty four indicator with an average 75%. Whereas obtain sufficient indicator category is the seventh indicator with an average 58.33%, the eighth indicator with an average 57.14%, indicator of nine with and average 42.86%, indicator of ten with an average 47.62%, indicator eleven with an average 46.43%, indicator fourteen with an average 42.86%, indicator fifteen with an average 45.24%. indicator seventeen with an average 58.33%, indicator twenty one with an average 53.57%, indicator twenty three with an average 51.19%.Keyword: competence of caregivers